THE EFFECTIVENESS OF THE CONTEXTUAL TEACHING AND LEARNING MODEL THROUGH WHATSAPP GROUP IN LEARNING MATHEMATICS - Sukma, Wa Ode Nurmala (Perspektif Ilmu Pendidikan, 2022)
This study aims to determine the effectiveness of the application of the contextual teaching and learning model through whatsaap groups in class IV mathematics learning by taking into account the indicators of achieving effectiveness, namely: learning implementation, student learning activities, and student responses. The type of this research is descriptive research. The population is all fourth grade students of Madrasah Ibtidaiyah (MI) in Sorong City for the 2021/2022 academic year. The sampling technique used cluster random sampling. Data collection techniques using observation and questionnaires. Observations were used to describe the implementation of learning and student learning activities, while questionnaires were used to describe student responses. Data analysis was carried out by describing the average achievement of effectiveness indicators consisting of the implementation of learning, student learning activities, and student responses. The results of the study indicate that the indicators of achievement of effectiveness, implementation of learning have been carried out well starting from the initial, core, and closing activities. Indicators of student learning activities are classified as very active. Indicators of student response are classified as very positive. Based on this, the application of the contextual teaching and learning model through whatsaap groups in fourth grade mathematics learning is effective.